Economic stress affects the human sex ratio: A retest of the Trivers–Willard hypothesis in Poland - Mikulec, Artur; Rosset, Iwona; Żądzińska, Elżbieta (Anthropological Review, 2023)
This paper contributes to the verification of the Trivers–Willard hypothesis (TWH). Based on the TWH, observed sex (male-to-female) ratio at birth in a population is presumed to decline when parents experience economic stress. The empirical evidence so far is mixed.The research material consisted of data on the total numbers of live male and female births in the Polish population in the years 1995–2020. The data were used to produce semiannual time series for secondary sex ratio (SSR), and the sex ratio at birth (SRB). The variable describing the economic stress of households was percentage change in private consumption. The statistical method proposed by Catalano and Bruckner – expanded to include additional statistical analyses – was applied to retest the economic stress hypothesis. The analysis led to complementary ARMAX models, explaining SSR or SRB variance based on autoregression and the moving average process, as well as private consumption. The results indicate that periods of decreasing consumption favored mothers having daughters, while periods of increasing consumption favored mothers having sons. The number of “additional” male births resulting from improved economic conditions was calculated for the period of study. Consequently, the economic factor was shown to have a positive effect on the human sex ratio. At the same time, it should be noted that SSR and SRB reaction lags to consumption changes were different for Łódzkie Province (one year) and for Poland (two years).The obtained results led to the “correct” verification of the Trivers–Willard hypothesis (TWH): economic stress affected the SSR and SRB in Poland. Both SSR and SRB were useful in analyzing economic stress (a dual solution). The use of a greater density of data points was shown to improve analysis effects and increase the likelihood of a “positive” verification of the economic stress hypothesis.